2009
DOI: 10.1504/ijetm.2009.023523
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and sustainability impact assessment in small islands: the case of Azores and Madeira

Abstract: This paper compares Environmental Impact Assessment (EIA) practices and effectiveness in the Portuguese islands of the Azores and Madeira. This was accomplished by qualitative appraisal and evaluation of the contents of EIA statements and the characterisation of the EIA practices. Data was collected from the islands' regional environmental agencies and from the Environmental Portuguese Agency internet database. The findings reveal that most EIA project practitioners and consultants in the islands are associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The results indicate that experts prefer having resources, human and financial, for the development of good practices and skills among practitioners. This preference intertwines with the importance given to topics considered in the questionnaire, such as guidelines, including scale guidelines, themes, assessment methods and indicators, which is consistent with what was previously suggested by Ramos et al (2009) andKerr (2005).…”
Section: Exploring Views and Perspectives Of European Small Islands Ssupporting
confidence: 86%
See 4 more Smart Citations
“…The results indicate that experts prefer having resources, human and financial, for the development of good practices and skills among practitioners. This preference intertwines with the importance given to topics considered in the questionnaire, such as guidelines, including scale guidelines, themes, assessment methods and indicators, which is consistent with what was previously suggested by Ramos et al (2009) andKerr (2005).…”
Section: Exploring Views and Perspectives Of European Small Islands Ssupporting
confidence: 86%
“…In addition, as highlighted by respondents, there is the possibility th on the SEA team. Though this could occur where the SEA system relies on consultants to develop the SEA process, as is the Portuguese case identified by Polido et al (2016), if the SEA is mainly developed by in-house practitioners, as observed by McLauchlan and João (2012) for the Scottish case, probably these practitioners may perceive the Nonetheless, the majority of the respondents stated that to have trained staff on SEA and sustainability-related issues is important in small islands, as suggested by Bass and Dalal-Clayton (1995) and Ramos et al (2009).…”
Section: Exploring Views and Perspectives Of European Small Islands Smentioning
confidence: 92%
See 3 more Smart Citations